The Mental Health Crisis in Higher Education: Insights from Singapore - Stanfield, Dave; Tay, Andrew (International Higher Education, 2024)
After the COVID-19 pandemic, tertiary students globally have continued to struggle with their mental health at alarming rates. Institutions struggle to respond adequately as the demand for professional counseling services continues to increase. Singapore’s higher education sector offers a number of insights, including innovative preventative approaches, an openness to piloting promising new technology, and the involvement of multiple institutional stakeholders.